Práticas intergeracionais e políticas públicas pró-envelhecimento na perspectiva de velhos: o caso da Vila Anglo-Brasileira - Novellino, Elias José (2019)
The participation of old people in productive practices for themselves and for the other generations has shown how they have everything to be successful. This research aims to investigate, in the light of the theoretical-methodological perspective of Gerontology, which means for the old people of the Anglo-Brazilian Village popular practices that take place in a public environment, and what their contribution to the coexistence with the aging itself \and that of other people. An interview was conducted with 10 elderly people, through a sociodemographic questionnaire and closed and open questions, in order to trace the profile of the subjects and to portray the reality of their daily lives. The academic record of the case of the Anglo-Brazilian Village has its importance in showing the protagonism of the old people in socio-political terms to mobilize, exercise their rights and duties, acting as social agents with other residents, sensitizing them to engage in fight for improvements in the neighborhood. Forgotten by the public power in the early 80's, the neighborhood is in the West Zone of São Paulo and has houses of middle class and other very poor. A popular movement was created to request from the Municipal and State government rights to the citizens and were won: public stairs (1982); basic health Unit, inaugurated in 1983; the child day care and the center of the child and adolescent in 1985 and the youth and adult education in 2009. The conquest of UBS's own building took 23 years, occurring in 2003 and has Educational and Therapeutic Groups that work under the coordination and / or help of the Elderly. The results of the interviews were analyzed based on from Paulo Freire's socio-educational approach, among other Gerontology theorists and other areas, who believe in social actions and validate them as well as to its transforming agents, among others, the classic Debert, Mucida, Messy, Agamben, and from the perspective of the Active Aging Policy. The results of the interviews show that the perception that in the old age people are not productive and happy, emphasizes how the organized population improves the living conditions of the people in every way; these intergenerational experiences can contribute to the field of research and practices in the field of aging and are seen as a good way for Social and Public Policies in favor of healthy, active aging